The Influence of Leadership Style and Workload on Employee Performance at PT Maju Rukun Bersama, Tangerang Regency - Gulo, Nelvin Metri; Senen, Senen (STEBIS Bina Mandiri, 2025)
This study aims to determine whether there is an influence of leadership style and workload on employee performance at PT. Maju Rukun Bersama either partially or simultaneously. This research method is associative with a quantitative approach, while the population used is 100 respondents and the sample used in this study is 100 respondents obtained from sample calculations using saturated samples. Data collection techniques using questionnaires, data analysis techniques with validity tests, reliability, classical assumption tests, multiple regression analysis, hypothesis tests, t-tests, f-tests, and coefficients of determination. The results of the study show that leadership style has a partial effect on employee performance as seen from the t-count value > t-table (15.757 > 1.984) with a value (sig) of 0.000 < 0.05 with a regression equation of Y = 0.846 + 0.780 X1. Workload has a partial effect on employee performance as seen from the calculated tvalue > ttable (14.582 > 1.984) with a value (sig) of 0.000 < 0.05 with the regression equation Y = 0.581 + 0.839 X2 and simultaneously leadership style and workload have an effect on employee performance as seen from the calculated Fvalue > Ftable (132.920 > 3.09) with a value (sig) of 0.000 < 0.05 with the regression equation Y = 0.621 + 0.512 X1 + 0.321 X2. Based on the results of the coefficient of determination, it has a contribution of 72.7% and the remaining 27.3% is influenced by other factors.